Philosophical Thought According to Al Farabi - Ainur Awaliah; Maspuroh; Muhammad Rakha Firjatullah; Putri Hafidzah (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2025)
Al-Farabi was a Muslim philosopher who systematically laid the foundation of the basic Islamic philosophy in detail and easy to understand for later generations. His philosophical thoughts were influenced by the Greek philosophy. According to him, the world occurs because the first entity (Allah) was abundant in stages called emanation. Philosophers acquired the truth by using the power of reasoning, while the prophets acquired it through God revelation to humans He chose. His thought in politics such as a major state resembles Plato's concept of ideal state. The leader is the first actor who brings citizen to happiness just like the function of the heart in a body with other organs acting as assistants to achieve the desired happiness.